Update on abortion policy. Issue 6 (December 2016) - Conti, Jennifer A.; Brant, Ashley R.; Shumaker, Heather D.; Reeves, Matthew F.
Abstract : Purpose of review: To review the status of antiabortion restrictions enacted over the last 5 years in the United States and their impact on abortion services. Recent findings: In recent years, there has been an alarming rise in the number of antiabortion laws enacted across the United States. In total, various states in the union enacted 334 abortion restrictions from 2011 to July 2016, accounting for 30% of all abortion restrictions since the legalization of abortion in 1973. Data confirm, however, that more liberal abortion laws do not increase the number of abortions, but instead greatly decrease the number of abortion-related deaths. Several countries including Romania, South Africa and Nepal have seen dramatic decreases in maternal mortality after liberalization of abortion laws, without an increase in the total number of abortions. In the United States, abortions are incredibly safe with very low rates of complications and a mortality rate of 0.7 per 100 000 women. With increasing abortion restrictions, maternal mortality in the United States can be expected to rise over the coming years, as has been observed in Texas recently. Summary: Liberalization of abortion laws saves women's lives. The rising number of antiabortion restrictions will ultimately harm women and their families.